Kidney-Targeted Cytosolic Delivery of siRNA Using a Small-Sized Mirror DNA Tetrahedron for Enhanced Potency - Thai Bao Dieu Hien; Kim, Kyoung-Ran; Hong, Kyung Tae; Voitsitskyi, Taras; Lee, Jun-Seok; Mao, Chengde; Ahn, Dae-Ro (AMER CHEMICAL SOC, 2020)
A proper intracellular delivery method with target tissue specificity is critical to utilize the full potential of therapeutic molecules including siRNAs while minimizing their side effects. Herein, we prepare four small-sized DNA tetrahedrons (sTds) by self-assembly of different sugar backbone-modified oligonucleotides and screened them to develop a platform for kidney-targeted cytosolic delivery of siRNA. An in vivo biodistribution study revealed the kidney-specific accumulation of mirror DNA tetrahedron (L-sTd). Low opsonization of L-sTd in serum appeared to avoid liver clearance and keep its size small enough to be filtered through the glomerular basement membrane (GBM). After GBM filtration, L-sTd could be delivered into tubular cells by endocytosis. The kidney preference and the tubular cell uptake property of the mirror DNA nanostructure could be successfully harnessed for kidney-targeted intracellular delivery of p53 siRNA to treat acute kidney injury (AKI) in mice. Therefore, L-sTd could be a promising platform for kidney-targeted cytosolic delivery of siRNA to treat renal diseases.